Extreme Surface Energy Budget Anomalies in the High Arctic in Winter - Murto, Sonja; Papritz, Lukas; id_orcid:0 000-0002-2047-9544; Messori, Gabriele; Caballero, Rodrigo; Svensson, Gunilla; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (American Meteorological Society, 2023)
In recent decades, the Arctic has warmed faster than the global mean, especially during winter. This has been attributed to various causes, with recent studies highlighting the importance of enhanced downward infrared radiation associated with anomalous inflow of warm, moist air from lower latitudes. Here, we study wintertime surface energy budget (SEB) anomalies over Arctic sea ice on synoptic time scales, using ERA5 (1979–2020). We introduce a new algorithm to identify areas with extreme, positive daily mean SEB anomalies and connect them to form spatiotemporal life cycle events. Most of these events are associated with large-scale inflow from the Atlantic and Pacific Oceans, driven by poleward deflection of the storm track and blocks over northern Eurasia and Alaska. Events originate near the ice edge, where they have roughly equal contributions of net longwave radiation and turbulent fluxes to the positive SEB anomaly. As the events move farther into the Arctic, SEB anomalies decrease due to weakening sensible and latent heat-flux anomalies, while the surface temperature anomaly increases toward the peak of the events along with the downward longwave radiation anomaly. Due to these temporal and spatial differences, the largest SEB anomalies are not always related to strongest surface warming. Thus, studying temperature anomalies alone might not be sufficient to determine sea ice changes. This study highlights the importance of turbulent fluxes in driving SEB anomalies and downward longwave radiation in determining local surface warming. Therefore, both processes need to be accurately represented in climate models. ISSN:0894-8755 ISSN:1520-0442